Involving caregivers in self‐management interventions for patients with heart failure and chronic obstructive pulmonary disease. A systematic review and meta‐analysis. (3rd September 2019) - Noonan, Miriam C.; Wingham, Jennifer; Dalal, Hasnain M.; Taylor, Rod S.
Abstract: Aim: To quantify the impact of involving caregivers in self‐management interventions on health‐related quality of life of patients with heart failure or chronic obstructive pulmonary disease. Design: Systematic review, meta‐analysis. Data sources: Searched: Medline Ebsco, PsycINFO, CINAHL, Embase, Web of Science, The British Library and ProQuest. Search time frame; January 1990–March 2018. Review Methods: Randomized controlled trials involving caregivers in self‐management interventions (≥2 components) compared with usual care for patients with heart failure or chronic obstructive pulmonary disease. A matched sample based on publication year, geographic location and inclusion of an exercise intervention of studies not involving caregivers were identified. Primary outcome of analysis was patient health‐related quality of life. Results: Thirteen randomized controlled trials (1, 701 participants: 1, 439 heart failure; 262 chronic obstructive pulmonary disease) involving caregivers (mean age 59; 58% female) were identified. Reported patient health‐related quality of life measures included; Minnesota Living with Heart Failure questionnaire, St. George's respiratory questionnaire and Short‐Form‐36. Compared with usual care, there was similar magnitude in mean improvement in patient health‐related quality of life with self‐management interventions in trials involving caregivers (SMD: 0.23, 95% confidence interval: −0.15–0.61) compared with trials without caregivers (SMD: 0.27, 0.08–0.46). Conclusion: Within the methodological constraints of this study, our results indicate that involving caregivers in self‐management interventions does not result in additional improvement in patient health‐related quality of life in heart failure or chronic obstructive pulmonary disease. However, involvement of caregivers in intervention delivery remains an important consideration and key area of research. Impact: Greater understanding and awareness is needed of the methodology of caregiver engagement in intervention development and delivery and its impact on patient outcomes. Abstract : 目的: 量化让护理人员参与对心力衰竭或慢性阻塞性肺疾病患者的自我管理干预措施这一举措会对患者健康相关生活质量产生的影响。 设计: 系统性评价、荟萃分析。 资料来源: 对Medline Ebsco、PsycINFO、CINAHL、Embase、科学网、大英图书馆以及ProQuest进行了检索。检索时间框架:1990年1月至2018年3月。 综述方法: 让护理人员参与对心力衰竭或慢性阻塞性肺疾病患者的自我管理干预措施这一举措(≥2个成分)与常规护理之间的随机对照试验。通过发表年份、地理位置和列入不涉及护理人员的研究的示范性干预措施, 确定了一个相匹配的样本。分析的主要成果是患者健康相关生活质量。 结果: 确定了13项涉及护理人员(平均年龄59岁;58%为女性)的随机对照试验(1701位受试者:1439例心力衰竭;262例慢性阻塞性肺疾病)。涵盖了所报告的患者健康相关生活质量指标:明尼苏达州心力衰竭生活调查问卷、圣乔治呼吸问卷以及简表36。与常规护理相比, 在有护理人员参与的试验(SMD:0.23, 95%置信区间:‐0.15至0.61)中采用自我管理干预措施对患者健康相关生活质量的平均改善程度与无护理人员参与的试验(SMD:0.27, 95%置信区间:0.08至0.46)相似。 结论: 在本次研究所用方法的限制下, 我们的结果表明, 在心力衰竭或慢性阻塞性肺疾病患者中, 让护理人员参与自我管理干预措施并不会导致患者健康相关生活质量得到额外改善。然而, 让护理人员参与提供干预措施, 仍然是一个重要的考虑因素和关键的研究领域。 影响: 需要对让护理人员参与制定和提供干预措施的方法及其对患者结局的影响有更深入的理解和认识。